Development of safety performance measures for different crashes severity at urban roundabouts - Taqwa I. Alhadidi; Mohammad Nour Al-Marafi; Asma Alazimi (Results in Engineering)
Roundabouts are widely utilized due to their perceived safety benefits compared to other unsignalized intersections. Studies have demonstrated that roundabouts are effective in reducing the frequency and severity of traffic crashes. However, the crash rate at roundabouts in Jordan has increased over time. A range of factors can influence the safety performance of roundabouts, including geometric and traffic characteristics. This study aims to quantify the impact of these factors on the safety of urban roundabouts in Amman, the capital of Jordan. To achieve this, three different crash severity prediction models were developed to assess the influence of various contributing factors. Data was collected from 16 roundabouts over a period of seven years, including traffic crashes, geometric characteristics, and traffic counts. Different models were tested, and the Negative Binomial (NB) model was found to be the best fit for traffic crashes frequency. The results indicate that an increase in entry width, inscribed diameter, entry path radius, entry angle, speed limit, number of approaches, weaving length, and weaving width are associated with an increase in roundabout crash risk. On the other hand, an increase in circular width, central diameter, and exit width is associated with a decrease in crash risks. The study also developed Crash Modification Factors (CMFs) using a cross-sectional method, which can be used to investigate the relationship between safety and geometric design features of roundabouts. The findings of this study can be used effectively to determine the appropriate intersection improvement strategies to enhance traffic safety conditions.